2021
DOI: 10.1186/s13047-021-00447-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐related foot disease in Australia: a systematic review of the prevalence and incidence of risk factors, disease and amputation in Australian populations

Abstract: Background Diabetes-related foot disease (DFD) is a leading cause of global hospitalisation, amputation and disability burdens; yet, the epidemiology of the DFD burden is unclear in Australia. We aimed to systematically review the literature reporting the prevalence and incidence of risk factors for DFD (e.g. neuropathy, peripheral artery disease), of DFD (ulcers and infection), and of diabetes-related amputation (total, minor and major amputation) in Australian populations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 63 publications
(285 reference statements)
3
48
0
Order By: Relevance
“…However, the incidence of in-patient admissions due to foot ulceration is much higher than the rest of the world, with diabetes related amputations being the highest amongst developed nations. A conclusion made from this data was that Australia is doing well to prevent DFU but not in managing them once they developed, resulting in high numbers of admissions and amputations due to diabetes related complications (3).…”
Section: Introductionmentioning
confidence: 95%
“…However, the incidence of in-patient admissions due to foot ulceration is much higher than the rest of the world, with diabetes related amputations being the highest amongst developed nations. A conclusion made from this data was that Australia is doing well to prevent DFU but not in managing them once they developed, resulting in high numbers of admissions and amputations due to diabetes related complications (3).…”
Section: Introductionmentioning
confidence: 95%
“…There is a paucity of data on DFD, without which it is hard to understand and assess the extent of their burden [20]. Zhang et al (2021) noted that very few studies in Australia reported the prevalence of different types of DFD [15,[21][22][23]. The studies that have been conducted on DFD have predominantly used the inpatient diabetes population, specific ethnic groups, or geographic areas [15,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…These studies could overestimate the prevalence burden, as they might represent people with diabetes who also have severe conditions [12]. This is supported by a systematic review conducted by Zhang et al (2021) that cast doubt on the accuracy of the reported prevalence and highlighted the necessity to undertake a large epidemiological study involving a representative population.…”
Section: Introductionmentioning
confidence: 99%
“…Foot infection is a common complication of diabetes and varies in severity [ 1 , 2 ]. Severe diabetes-related foot infection (DFI) often precipitates hospital admission and requirement for lower extremity amputation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: Clinical practice, Diabetic foot disease, Orthopaedic surgery, Survey, Vascular surgery Background Foot infection is a common complication of diabetes and varies in severity [1,2]. Severe diabetes-related foot infection (DFI) often precipitates hospital admission and requirement for lower extremity amputation [3].…”
mentioning
confidence: 99%